Analysis of Competitiveness Traditional Retail To Modern Retails in Consumer Perspective - Sunaryati Hardiani; Nanik Sisharinia (International Conferences SDGs 2030 Challenges and Solutions, 2030)
Competition in the retail industry can be seen in many ways, there are competition between traditional retail and modern retail, competition between modern retailers fellow and competition among traditional retails. The large presence of modern retailers in the region forced traditional retail to compete with the modern retailers. This study discusses how traditional retail competitiveness with the modern retail focused on consumer preferences aspects. Variables used to measure consumer preferences are Human Resource with indicators Appearance of shopkeeper, Hospitality in service, Speed in service, Shop open time, while Merchandise variable with indicator, Appearance store, Merchandise display, Number of products available, Diversity of product type, Diversity Brands are sold. Method of analysis with descriptive analysis. The research results show that hospitality in service, speed in service and certainty of shop opening time of traditional retail stores need to be improved. As for the number of products available, the diversity of product types and the diversity of brands sold is a problem that stems from the limitations of traditional retail capital. The government already has a solution that with the opening of credit access to financial institutions with the issuance of OJK Regulation no. 76 / POJK.07 / 2016 on Increasing Literacy and Financial Inclusion in the community.